Trends and the future of computerized printing systems: a forecast of technology development and its application in printing production - Zenkin, Mykola; Ivanko, Andrii; Kokhanovskyi, Vasyl (Technology audit and production reserves, 2023)
The object of research is computerized polygraphic systems, their technologies, current development trends and prospects for application in modern polygraphic production. The study solves the problem of determining current trends in the field of computerized printing systems, as well as developing forecasts for their future, taking into account modern technological innovations and the possibility of their application in printing. It was determined that the modern world is experiencing rapid technological changes. The integration of computer technologies in various branches of production not only optimizes processes, but also opens up new opportunities for development and innovation. The results were obtained: it was found that computerized polygraphic systems are becoming more and more widespread, providing the opportunity to improve product quality, reduce production costs and increase productivity. It has been proven that modern printing technologies demonstrate an impressive dynamic of progress, taking place in the context of intensive development of information and communication industries. The printing industry adapts quickly, assimilating modern technological advances and immediately implementing them into the production process. It has been confirmed that computer printing systems are actively developing, responding to the increase in market requirements and contributing to the improvement of print quality. Today's technologies, including 3D and 4D printing, digital stencil technology, laser engraving and central print management system (CPMS), are already integrated into the printing industry, providing automation, precision and efficiency. The obtained research results make it possible to ensure the industrial production of more individual, multifunctional and flexible products, expanding the horizons for printing companies. Forecasting the development of technologies and their application in printing production allows companies to always be one step ahead of competitors, rationally invest in innovation and effectively respond to changing market conditions. Given the globalization of the market and the growing demands for the quality of printing products, the ability to anticipate future trends and adapt to them is becoming a key success factor for manufacturers.